Fibromyalgia syndrome in mothers of children with cerebral palsy and its relationship with caregiver burden: a cross-sectional study - Aykurt Karlıbel, İlknur and Kasapoğlu Aksoy, Meliha and Yeni, Merve (The European Research Journal, 2024)
Objectives: Fibromyalgia syndrome (FMS) is a stress-related disease. The birth of a child with cerebral palsy (CP) is an important stress factor for the mother. This study aims to investigate the incidence of FMS in mothers of children with CP by comparing it with the control group and determining the factors affecting the severity of FMS. Methods: The study included 112 children with CP (age: 38-216 months), their caregiver mother (age: 23-50 years) (Group 1) and 52 non-disabled children (age: 40-180 months), their caregiver mothers (age: 27-50 years) (Group 2). Children were evaluated with the Gross Motor Function Classification System (GMFCS) and the functional independence scale for children (WeeFIM). The mothers were evaluated according to the 2010 ACR FMS diagnostic criteria. The FMS Impact Questionnaire (FIQ), the Hospital Anxiety and Depression Scale (HADS), and the Bakas Caregiving Outcomes Scale (BCOS) were applied. Results: In Group 1, mothers had higher anxiety-depression scores and caregiving burden than Group 2 (p < 0.05). FMS rate was %31.3 in Group 1 and %5.7 in Group 2. Mothers’ anxiety-depression scores, widespread pain index, symptom severity score, pain, and caregiver burden were higher in Group 1 than in Group 2 (p < 0.05). Factors affecting the severity of FMS are the number of siblings of children with CP, the number of siblings with CP, GMFCS, dependence level, anxiety-depression levels of mothers, and caregiver burden. The most influential factor is the caregiver burden. Conclusions: Long-term heavy caregiver burden in mothers of children with CP may be effective in developing FMS.